2021
DOI: 10.2147/cia.s340432
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Risk Factors of Age-Related Hearing Loss Among Malaysian Community‐Dwelling Older Adults

Abstract: Purpose: This study evaluates the prevalence of and the multidimensional risk factors associated with age-related hearing loss (ARHL) among community-dwelling older adults in Malaysia. Patients and Methods: A total of 253 participants aged 60 years and above participated in this cross-sectional study. The participants were subjected to pure tone audiometric assessment. The hearing threshold was calculated for the better ear and classified into pure-tone average (PTA) for the octave frequencies from 0.5 to 4 kH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…As previously discussed, several comorbidities, such as obesity and cardiovascular diseases, may accelerate hearing loss by disrupting blood flow in the inner ear [94,95]. Gopinath et al reported that high glucose and total carbohydrate diets among older adults were associated with an increased risk of developing hearing loss [61,96].…”
Section: Low Sugar and Caloric Restriction Dietmentioning
confidence: 99%
“…As previously discussed, several comorbidities, such as obesity and cardiovascular diseases, may accelerate hearing loss by disrupting blood flow in the inner ear [94,95]. Gopinath et al reported that high glucose and total carbohydrate diets among older adults were associated with an increased risk of developing hearing loss [61,96].…”
Section: Low Sugar and Caloric Restriction Dietmentioning
confidence: 99%
“…Fasted venous blood (overnight fasting of at least 8 h) was collected from each participant by a trained phlebotomist, as described previously [12]. Then, the blood samples were sent to an accredited clinical diagnostic laboratory for biochemical analysis.…”
Section: Blood Samples Collection and Biochemical Analysismentioning
confidence: 99%
“…A survey of the Korean population showed that smokers with diabetes had a higher risk of developing ARHL than non-smokers with diabetes [ 67 ]. In the Malaysian population, an increased risk of ARHL was linked to an increased waist circumference, decreased niacin and potassium intake, and increased carbohydrate intake [ 68 ]. Intermittent hypoxic conditions, high-fat diet, and galactose injections accelerate the aging of cochlear HCs in mice [ 69 ].…”
Section: Major Causal Factors Of Arhlmentioning
confidence: 99%